Attawapiskat: The Politics of Emergency - Spady, Samantha
This thesis investigates the politics of representation of Indigenous peoples in Canadian media. Using a case study of the 2011 housing crisis at Attawapiskat First Nation, I argue that emergency on reserve is constructed as Indigenous failure in mainstream print media and that these discourses work to construct a racialized national imaginary. Canadians are produced as benevolent through learning about Indigenous failure, and through their own capacity to assist and care for them. I have argued that this is a nation building practice of settler colonialism; it is inextricably linked to reclaiming ownership of land, and manufacturing legitimacy for the Canadian nation. This thesis traces these constructions through both mainstream, and alternative and independent media, and follows how these discourses invite white Settlers into a position of racial superiority. Examining ideas of goodness and innocence that condition Canadian identity, I offer strategies and limitations for anti-colonial engagement with Indigenous emergency. MAST